Pengaruh Penerapan Model Pembelajarankooperatif Tipe ThinkeTalksWrite (TTW) Terhadap Kemampuan Komunikasi Matematisy Pesertay Didik Kelas VIII SMP Negeri 7 Padang - MELATI . . (Departemen Matematika, 2019)
bThe application ofnthe cooperative learning model Think Talk Write can improve student learning outcomes, especially students' mathematical communication skills. This research was conducted with the aim of 1) knowing and describing mathematicalvcommunicationyskills ofpstudentsuwhonlearn with the cooperativeelearningmmodel TTW typerbetter than mathematicalycommunicationtskillsrof studentswwhoqlearn with direct learningxmodels, 2) knowing and describing how mathematical communication skills of students during applying the TTW type of cooperative learning model. The method used is a quasi-experimental and descriptive method with the Static Group Design. This study uses two classes for sample classes which before determining the sample class, first conduct a normality test, and the homogeneity test for variance can then be determined in terms of the population average similarity. After analyzing the data, the results of the study are 1) mathematicalccommunicationzskillsiof studentsgwho9learnewith the cooperative7learning6model TTW typetare better thanemathematical communicationmeskillswof5students6lwhorilearn5lwithnkdirect3llearningmodels,2)kmathematicalcommunicationrskillstof students in general have increased from each meeting. Key words- Students’ Mathematical Communication skills, Think Talk Write (TTW), Direct of Learning Model